COST ANALYSIS OF MINI HYDRO POWER PLANT USING BACTERIAL SWARM OPTIMIZATION - Çelikdemir, Soner; Yıldırım, Burak; Özdemir, Mahmut Temel (Zülküf GÜLSÜN [EN], 2017)
According to the 2023 vision determined by Turkey, which is one of the G20 countries, it aims to evaluate of the hydro power potential in terms of technical and economic making medium and large hydro power plants. Turkey's mini and micro hydro power potential isn’t fully evaluated as a number of countries.  In this context, empirical formula for cost analysis of mini and micro hydro power plants, which are becoming increasingly important, have been developed in this work with the aim of facilitating economic analysis. The developed equation is found by modified Bacterial Swarm Optimization (BSO) algorithm. When analyzed with the literature data, the obtained equation can calculate the costs with the least mistakes.